Repose time patterns of debris‐flow events in alpine catchments. Issue 5 (16th January 2023) - Heiser, Micha; Schlögl, Matthias; Spangl, Bernhard; Fuchs, Sven; Rickenmann, Dieter; Zimmermann, Markus; Scheidl, Christian
Abstract: The omnipresent threat of natural hazards in mountainous regions has led to a risk culture which requires knowledge about the frequency of the considered hazardous process. Observations suggest that the frequency of debris‐flow events in a single catchment is, besides climatic thresholds, also controlled by its geological, lithological and geomorphological characteristics. Based on investigations of debris‐flow event frequencies from 47 headwater catchments, our results support the classification of recurrence intervals as irregular, clustered or regular, originally proposed by Zimmermann et al. in 1997 ( Eclogae Geologicae Helvetiae, 90 (3), 415–420). However, instead of using geomorphological characteristics, our classification relies on quantitative analyses considering potential dependencies between events based on their inter‐event (repose) times. By employing a modified dynamic threshold concept with respect to debris‐flow initiation, we show that for irregular frequencies neither climatic nor geomorphological thresholds are altered by the last debris‐flow event. For regular and clustered time series, however, mutual dependency between events is reasonable and therefore prompts dynamic changes of climatic as well as geomorphological thresholds. Abstract : Based on quantitative analyses of the inter‐event (repose) times of debris‐flow events from 47 headwater catchments, our results support the classification of recurrence intervals as irregular, clustered or regular. By employing a modified dynamic threshold concept with respect to debris‐flow initiation, we show that for irregular frequencies neither climatic nor geomorphological thresholds are altered by the last debris‐flow event. For regular and clustered time series, however, mutual dependency between events is reasonable and therefore prompts dynamic changes of climatic as well as geomorphological thresholds.